1997
DOI: 10.1021/ja962374r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Waters of Hydrophobic Hydration by Microwave Dielectric Relaxation

Abstract: In the present paper, a temperature dependent dielectric relaxation near 5 GHz (at a frequency just lower than that of bulk water) is observed in aqueous solutions of hydrophobic elastic protein-based polymers, such as (GVGVP) 251 and (GV-GIP) 260 . On dilution at low temperatures of the solution, this relaxation becomes more intense approaching different hydrophobicity dependent limits as the hydrophobicity increases from Val (V) with the side chain -CH(CH 3 ) 2 to Ile (I) with the addition of a CH 2 moiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
81
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 23 publications
6
81
0
1
Order By: Relevance
“…They are also consistent with recent MD simulations of an elastin-like polypeptide, (VPGVG) 18 . The discrepancy with the somewhat larger MD backbone amide order parameters (S Ï­ 0.51) (25) is likely due to the much shorter time scale (Ïł10 ns) of the MD calculations compared with that of the NMR experiment (Ïł50 s).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…They are also consistent with recent MD simulations of an elastin-like polypeptide, (VPGVG) 18 . The discrepancy with the somewhat larger MD backbone amide order parameters (S Ï­ 0.51) (25) is likely due to the much shorter time scale (Ïł10 ns) of the MD calculations compared with that of the NMR experiment (Ïł50 s).…”
Section: Discussionsupporting
confidence: 91%
“…polypeptide chains are completely disordered with a gaussian distribution of end-to-end distances. Backbone motions were confirmed by dielectric (18) and NMR (19 -21) relaxation studies that focused on the time scale of the dynamics. In addition, from the absence of intrinsic birefringence, it was concluded that elastin is isotropic and devoid of structure at the molecular level (22,23).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Recently several groups used the time dependent Stokes shift 5-10 , pulsed NMR and dielectric relaxation techniques [11][12][13][14] to unravel the dynamics of the water molecules in various organized media such as cyclodextrins 5,6 , reverse micelle 4,7-9 and micelles. 10 The results of the dynamic Stokes shift studies indicate that while ordinary water molecules relax in the subpicosecond time scale, inside these organized assemblies the solvation dynamics becomes several thousand times slower and occurs in the nanosecond timescale.…”
mentioning
confidence: 99%
“…[1][2][3] The behavior of water molecules present at such interfaces and perturbed by local electrostatic and hydrogen bond interactions are of special interest because of the unique role played by the water molecules in many biological processes. Recently several groups used the time dependent Stokes shift [5][6][7][8][9][10] , pulsed NMR and dielectric relaxation techniques [11][12][13][14] to unravel the dynamics of the water molecules in various organized media such as cyclodextrins 5,6 , reverse micelle 4,7-9 and micelles. 10 The results of the dynamic Stokes shift studies indicate that while ordinary water molecules relax in the subpicosecond time scale, inside these organized assemblies the solvation dynamics becomes several thousand times slower and occurs in the nanosecond timescale.…”
mentioning
confidence: 99%